Discovery of indole inhibitors of chemokine receptor 9 (CCR9). Issue 14 (15th July 2016) - Pandya, Bhaumik A.; Baber, Christian; Chan, Audrey; Chamberlain, Brian; Chandonnet, Haoqun; Goss, Jennifer; Hopper, Timothy; Lippa, Blaise; Poutsiaka, Katherine; Romero, Jan; Stucka, Sabrina; Varoglu, Mustafa; et al.
Graphical abstract: Abstract: Irritable bowel diseases (IBD) such as Crohn's disease (CD) and ulcerative colitis (UC) are serious chronic diseases affecting millions of patients worldwide. Studies of human chemokine biology has suggested C–C chemokine receptor 9 (CCR9) may be a key mediator of pro-inflammatory signaling. Discovery of agents that inhibit CCR9 may lead to new therapies for CD and UC patients. Herein we describe the evolution of a high content screening hit (1 ) into potent inhibitors of CCR9, such as azaindole12 .